The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1519-69842012000100027
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and biology of Dinocampus coccinellae (Schrank, 1802) (Hymenoptera; Braconidae: Euphorinae) parasitising different species of Coccinellidae (Coleoptera) in Neotropical region

Abstract: Surveys on Coccinellidae (Coleoptera) in Sete Lagoas city, Minas Gerais state, Brazil, indicated the parasitism of adults of the species Coleomegilla maculata De Geer, 1775, Eriopis connexa (Germar, 1824)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…In Brazil, for example, the few records available were made by Gravena (1978), Berti-Filho & Costa (1995) and Silva et al (2012). Here, we describe new records of coccinellid parasitoids with emphasis on new host-parasitoid interactions in two biomes considered hotspots of biodiversity in Brazil.…”
mentioning
confidence: 84%
“…In Brazil, for example, the few records available were made by Gravena (1978), Berti-Filho & Costa (1995) and Silva et al (2012). Here, we describe new records of coccinellid parasitoids with emphasis on new host-parasitoid interactions in two biomes considered hotspots of biodiversity in Brazil.…”
mentioning
confidence: 84%
“…Larvae of these predators may complete their development with prey that are not aphids but this is poorly studied, although eggs of Coleoptera and Lepidoptera have been used as alternative prey for them (Silva et al, 2009(Silva et al, , 2010(Silva et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that this parasitoid displays preference for moving individuals (Berkvens et al 2010, Silva et al 2012). Therefore, the low number of attacks in the third instar, fourth instar and pupa stages may be related to the lower mobility of these stages.…”
Section: Discussionmentioning
confidence: 99%
“…According to Silva et al (2012), D. coccinellae can even parasitize Coleomegilla maculata (De Geer, 1775), Eriopis connexa (Germar, 1824), and Olla v-nigrum (Mulsant, 1866), which are native species that can influence in the development time of this parasitoid.…”
mentioning
confidence: 99%